PERKEMBANGAN BAHASA ANAK MENGGUNAKAN METODE BERCERITA - Nur Fitria Desiani; Suleha Ecca; Suardi Zain (Universitas Negeri Makassar, 2024)
This study aims to analyze children's language development by providing stimulus in the form of storytelling. This research uses a descriptive method with a qualitative approach. The focus of this research is children's language development using the storytelling method in Group B students of Aisyiyah 1 Baranti Kindergarten. The data in this study are all vocabulary spoken by children. The data source is group B children at Aisyiyah 1 Baranti Kindergarten, totaling 19 children. The data collection techniques were observation, interview, and documentation. The collected data were analyzed using descriptive statistics. The results showed that children's vocabulary developed with each stimulus given. The stimulus given plays a big role in the development of children's vocabulary. However, the selection of themes in the storytelling method determines the results of the development of children's vocabulary. The data obtained in this study are 5,769 nouns, 2,722 verbs, 1,034 adjectives, 343 adverbs, 971 numeralia, 302 task words, and 330. So the total vocabulary spoken by children is 11,480.